ESENSI PROKRASTINASI FUNGSIONAL MEMBENTUK INFORMATION LITERACY SELF-EFFICACY MAHASISWA TINGKAT AKHIR PROGRAM STUDI ILMU PERPUSTAKAAN DI INDONESIA - Septiono, Trimo (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
The process of writing a thesis for final year students of the library science study program provides a new platform for developing the ability to manage information to become new knowledge. It is often mentioned that writing a thesis presents its own challenges for students at every stage. The emergence of functional procrastination activity is no exception. The purpose of this study is to describe the essence of functional procrastination activities in the thesis writing process, both individually and in groups. The research method used is descriptive with a qualitative approach involving library science students from two universities as informants. The results showed that functional procrastination activity is an unavoidable but can be minimized part. This condition occurs because students have difficulty in analyzing and determining information based on their information needs. In general, functional procrastination activities have a positive essence on perfecting the results of the thesis, but it should be understood that these conditions need to be minimized considering the limited processing time and the expiration duration of the data held. In addition, the results of the study also found that a series of processes for completing thesis writing by students is a platform for developing information literacy self-efficacy.